De novo atrial fibrillation as an independent prognostic marker after ST-segment elevation myocardial infarction: Results from the RIMA registry. Issue 2 (August 2019) - Gourronc, Youna; Grall, Sylvain; Ingremeau, Delphine; Desprets, Laurent; Prunier, Fabrice; Furber, Alain; Bière, Loïc
Highlights: Atrial fibrillation is common in ST-segment elevation myocardial infarction but with uncertain impact on prognosis. Only de novo atrial fibrillation was associated with 1-year cardiovascular mortality. De novo atrial fibrillation should be considered as a strong prognostic marker. Abstract: Background: Atrial fibrillation (AF) is common in ST-segment elevation myocardial infarction (STEMI), but its influence on prognosis remains controversial. Aim: We examined the 1-year prognostic value of AF in STEMI, distinguishing patients with prior AF from patients with de novo AF. Methods: Between January 2004 and December 2015, 3173 STEMI patients were enrolled in the RIMA registry ( Registre des Infarctus en Maine Anjou ). They were divided into 3 groups: (1) AF-free patients; (2) patients with known prior AF; and (3) patients with de novo AF during hospitalization (including admission). We defined 3 primary outcomes at 1-year post-discharge: cardiovascular mortality, readmission for heart failure (HF), and stroke. Temporal onset of de novo AF was also studied. Results: A total 158 patients (5%) had prior AF, and 278 (8.8%) presented de novo AF. Prior AF patients were significantly older [81 (73;86) years] with more comorbidities, but de novo AF patients presented with a greater creatine kinase peak and lower left ventricular ejection fraction [LVEF = 44 (35;50)% for de novo AF vs 50 (40;55)% for prior AF, p < 0.001]. At 1-year follow-up, cardiovascular mortality was higher in cases of AF (13.5% for prior AF vs 9.2% for de novo AF, compared with 2.4% for AF-free patients, p < 0.001). After adjustments, only de novo AF was correlated with cardiovascular mortality (hazard ratio 2.49; 95% CI 1.32–4.67; p = 0.004), but both types of AF were correlated with readmission for HF. There was no significant difference in respect of stroke between prior AF, de novo AF, and AF-free (2.2%, 0.5%, and 0.8%, respectively, p = 0.327). Finally, outcomes did not differ between AF occurring <24 h after admission ( n = 127) and de novo AF occurring within ≥24 h ( n = 151). Conclusion: De novo AF was independently associated with 1-year cardiovascular mortality. It should not be considered as an intercurrent event of STEMI, but rather as a strong prognostic marker.